B(C6F5)3/Amine‐Catalyzed C(sp)−H Silylation of Terminal Alkynes with Hydrosilanes: Experimental and Theoretical Studies. Issue 46 (17th October 2018) - Ma, Yuanhong; Lou, Shao‐Jie; Luo, Gen; Luo, Yong; Zhan, Gu; Nishiura, Masayoshi; Luo, Yi; Hou, Zhaomin
Abstract: Transition metal catalyzed C−H functionalization of organic compounds has proved to be a useful atom‐efficient strategy in organic synthesis. In contrast, main‐group‐element‐based catalytic processes for C−H functionalization have remained underexplored to date. Reported herein is the catalytic C(sp)−H silylation of a wide range of terminal alkynes with hydrosilanes by using a combination of B(C6 F5 )3 and an organic base such as triethylenediamine (DABCO). This protocol constitutes the first example of boron‐catalyzed C(sp)−H functionalization, offering a convenient route for the synthesis of a variety of alkynylsilanes. Experimental and computational studies have revealed that DABCO plays two crucial roles (Lewis base and Brønsted base) in this catalytic transformation. Abstract : Double duty : The combination of B(C6 F5 )3 and an organic base, such as triethylenediamine (DABCO), serve as an excellent catalytic system for the C(sp)−H silylation of terminal alkynes with hydrosilanes. DABCO plays two crucial roles (Lewis base and Brønsted base) as revealed by experimental and DFT studies.